KOMPARASI ASIMETRI INFORMASI SEBELUM DAN SESUDAH KONVERGENSI IFRS (STUDI KASUS PADA PERUSAHAAN AGRICULTURE DAN MINING YANG TERDAFTAR DI BEI) - Rahayu, Retno; Dewi Cahyati, Ari (Widya Warta, 2015)
Indonesia as a member of the G20 countries decided to converge to IFRS. Convergence process was carried out in stages and ended in 2012. One of the objectives of convergence ofIFRS was to improve the quality of financial reporting, including the reduction of information asymmetry. The aim of this study is to examine whether or not there are some differences in information asymmetry before and after the convergence of IFRS. The sample is 17 companies in the sectors of agriculture and mining listed in Indonesia Stock Exchange. In this case, the companies already published the date of submission of the financial statements of the year 2001-2012. This research applied descriptive comparative method, which comparedinformation asymmetry before and after the convergence ofÂ  IFRS. The data were analyzed using paired sample t test technique. The results of analysis showed that there was nosignificant difference in information asymmetry before and after the convergence of IFRS.